MODEL PENGALAMAN KERJA DALAM UPAYA MENINGKATKAN MOTIVASI KERJA KARYAWAN PABRIK KELAPA SAWIT (PKS) PT. ELUAN MAHKOTA DI KABUPATEN ROKAN HULU - Seprini; Yulfita Aini (Jurnal Ilmiah Cano Ekonomos, 2021)
Work experience is the process of forming knowledge and the level of mastery of one's knowledge and skills in their work that can be measured from their working period and the level of knowledge and skills they possess. Work experience in a Palm Oil Mill (PKS) is largely determined by the length of time or work period that has been taken by someone to be able to understand the tasks that are in the Palm Oil Mill to undergo certain jobs. Regarding how long the minimum work experience that must be owned by someone to become a leader or manager in a particular organization is still uncertain. The level of knowledge and skills possessed by a worker largely determines the high low work experience of employees in Palm Oil Mills (PKS). This study seeks to conduct an experimental study of the level of work experience of Palm Oil Mill (PKS) employees in Rokan Hulu Regency so that it is hoped that they will be able to find the right concept in managing the work experience of Palm Oil Mill (PKS) employees, especially for Rokan Hulu Regency. Data analysis technique in this research is to use quantitative descriptive analysis techniques. This analysis aims to describe at a glance the results of research respondents, the mean value (mean) of each question item and the total item. Besides this analysis is used to determine the achievement of respondents to the spread of respondents' answers to the question items used. Thus the percentage and activities of the respondents' achievement will be drawn. Based on the results of analysis of research data that has been done, the work experience of the employees of the Palm Oil Mill (PKS) of PT. Eluan Mahkota in Rokan Hulu Regency is in good condition, seen from the TCR level for respondents' responses regarding work experience variables of 86.17% with a good statement level. This means that indicators of work experience in the Palm Oil Mill (PKS) of PT. Eluan Mahkota (EMA) in Rokan Hulu Regency was stated by respondents as good. Work experience in this study was measured using indicators of length of work, work experience, skills and mastery of work and equipment.